New alternative realizations of a cross coupled quadruplet bandpass filter - Kuo, J.-T. (Institute of Electrical and Electronics Engineers Inc., 2019)
New alternative realizations of a quadruplet bandpass filter are investigated. The feasibility of these new alternative coupling schemes is validated by two-port Y-parameters of the lowpass prototype network with constant inverters. Two experimental circuits are fabricated and measured. Good agreement between measured responses and simulated data validates the concept. Â© 2019 IEEE.